STUDI KOMPARATIF PENETAPAN TARIF JASA RAWAT INAP DENGAN METODE BIAYA TRADISIONAL DAN ACTIVITY BASED COSTING (STUDI KASUS PADA UPTD PUSKESMAS POMALAA KABUPATEN KOLAKA) - Andi, Mutiara Sari; Kartomo, Kartomo; Ilham, Surianto (Komunitas Manajemen Kompetitif, 2025)
Study Komperatif Determination of Inpatient Service Rates Using Traditional Cost Methods and Activity Based Costing (Case Study at UPTD Pukesmas Pomalaa, Kolaka Regency). This study aims to determine the method of setting inpatient service rates using the traditional cost method and to determine the method of setting inpatient service rates using the activity based costing method at the Pomalaa Health Center UPTD, Kolaka Regency. Field research and library research were the research methods used in this study. Researchers employ observation, interviews, and documentation analysis as data collection methods. In order to determine inpatient service rates using the activity-based costing method, this study employed quantitative descriptive analysis as its data analysis tool. The results of this study indicate that the inpatient service rates using the activity based costing method when compared to the inpatient service rates that have been set by the BLUD UPTD Pomalaa Health Center currently using the traditional method, then using the activity based costing method provides higher rates for class 1 inpatient care. With a difference of Class I Rp 182,947. Keywords: Service Rates, Traditional Method, Activity Based Costing Method.